Upaya Peningkatan Nilai Tambah Ikan Bandeng Menjadi Abon Bandeng di La Primarasa di Desa Balun Kecamatan Turi Kabupaten Lamongan - Sa'adah, Wachidatus (Universitas Galuh, 2024)
The availability of milkfish during the season will be abundant, and cause the price of fish to fall, to anticipate it, the La Primarasa household industry in Lamongan makes fish floss from milkfish. This effort is carried out with the aim of increasing the added value of milkfish. This study is a quantitative research with the purposive sample method in selecting the sample, and using the calculation of added value analysis. The results of the study obtained that the amount of added value from processed milkfish into milkfish floss La Primarasa is Rp12,000/kg with an added value ratio of 24%.